2008
DOI: 10.1121/1.2935015
|View full text |Cite
|
Sign up to set email alerts
|

Development of low noise tyres in EC project SILENCE

Abstract: A lot of efforts were made in the last two decades to lower the tire/road noise. The tire industry has optimized the tread pattern as the main influence parameter so that nowadays the radiated sound pressure of a modern tire in the far field is very close to that of a blank tire with the same construction. Because the tread pattern is needed to achieve the required safety level further noise reduction has to be addressed mainly by tire construction. For many years tire manufacturers have been searching for a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Optimizing one performance often affects another performance negatively. A trade-off between noise, wear and hydroplaning is shown to exist [170], [167]. Seamann showed that more grooves increase the water storage capacity improving the hydroplaning performance.…”
Section: Tyre Performancesmentioning
confidence: 99%
“…Optimizing one performance often affects another performance negatively. A trade-off between noise, wear and hydroplaning is shown to exist [170], [167]. Seamann showed that more grooves increase the water storage capacity improving the hydroplaning performance.…”
Section: Tyre Performancesmentioning
confidence: 99%